A new record of the rare Bigeye Sand Tiger shark Odontaspis noronhai Maul, 1955 (Lamniformes: Odontaspididae) from the northwestern Pacific, with notes on dentition - Ng, Shing-Lai; Yu, Chi-Ju; Su, Shan-Hui; Joung, Shoou-Jeng (Zootaxa, 2022)
In the Pacific Ocean, the rare Bigeye Sand Tiger shark Odontaspis noronhai has only been recorded twice, once from its central and once from its eastern part. Here we report the first record of this species from the northwestern Pacific. This specimen measuring 312 cm total length (TL) was captured off northeastern Taiwan (25°25’N, 124°10’E) from a depth of 100 m (in waters over 2100 m deep) in mid-December 2019, and was retrieved on 27 December 2019 when landed in port. Photo of the fresh specimen along with morphometric and meristic data and DNA information are provided herein. Dentition of the specimen is different from all other specimens by having two cusplets on at least one side of cusps on most of the teeth (vs. only one cusplet per side), and lower total tooth count (29/29 vs. 34–38/37–46). This record documents an extended distribution (about 7864 km westward from the central Pacific Ocean), and provides strong evidence for the wide distribution and mesopelagic characteristic of this poorly known species.